Low prevalence of maternal microchimerism in peripheral blood of Japanese children with type 1 diabetes. Issue 12 (7th January 2020) - Ushijima, K.; Okuno, M.; Ayabe, T.; Kikuchi, N.; Kawamura, T.; Urakami, T.; Yokota, I.; Amemiya, S.; Uchiyama, T.; Kikuchi, T.; Ogata, T.; Sugihara, S.; et al.
Abstract: Aim: To clarify the prevalence and degree of maternal microchimerism in Japanese children with type 1 diabetes, as well as its effect on phenotypic variation. Methods: We studied 153 Japanese children with type 1 diabetes, including 124 children positive for β‐cell autoantibodies, and their 71 unaffected siblings. The number of circulating microchimeric cells per 10 5 host cells was estimated by the use of quantitative‐polymerase chain reaction targeting non‐transmitted maternal human leukocyte antigen alleles. The results were compared to previous data from white European people. Phenotypic comparison was performed between maternal microchimerism carriers and non‐carriers with diabetes. Results: Maternal microchimerism was detected in 15% of children with autoantibody‐positive type 1 diabetes, 28% of children with autoantibody‐negative type 1 diabetes, and 16% of unaffected siblings. There were no differences in the prevalence or levels of maternal microchimerism among the three groups or between the children with type 1 diabetes and their unaffected siblings. Furthermore, maternal microchimerism carriers and non‐carriers exhibited similar phenotypes. Conclusions: Maternal microchimerism appears to be less common in Japanese children with type 1 diabetes than in white European people. Our data indicate that maternal microchimerism is unlikely to be a major trigger or a phenotypic determinant of type 1 diabetes in Japanese children and that the biological significance of maternal microchimerism in type 1 diabetes may differ among ethnic groups. What's new?: Maternal microchimerism appears to be less common in Japanese children with type 1 diabetes than in white European people with this condition. Circulating microchimeric cells are unlikely to be a major trigger or a phenotypic determinant of type 1 diabetes in Japanese children. The biological significance of maternal microchimerism in type 1 diabetes may differ among ethnic groups.